Performans Produksi dan Profil Metabolik Darah Domba Garut dan Jonggol yang Diberi Limbah Tauge dan Omega-3 (PRODUCTION PERFORMANCE AND BLOOD METABOLIC PROFILES OF GARUT AND JONGGOL RAMS THAT WAS FED MUNG BEAN SPROUT WASTE AND OMEGA-3) - Wijaya, Gagah Hendra; Yamin, Mohamad; Nuraini, Henny; Esfandiari, Anita (Jurnal Veteriner, 2016)
The research objectives were to evaluate and compare of production performances and blood metabolicprofiles of garut and jonggol rams fed with mung bean sprout waste and omega-3. This research used 24rams aged of 1-2 years, consisted of 12 garut rams weighed of 36,43±1,45 kg (CV=13,87%) and 12 jonggolrams weighed of 23,09±0,57kg (CV=8,64%). Research used Completely Randomized factorial Design(CRD 2x3) with 2 main treatments x 3 factorials and four replications. The first factors as the maintreatments were different breeds of garut and jonggol. The second factors as the factorial treatments werethree different feed percentages which consisted of P0 (40% grass+60% concentrate I), P1 (40% mung beansprouts waste+60% concentrate II), and P2 (40% mung bean sprouts waste+60% concentrate II+omega-3).Data were analyzed by analysis of variance (ANOVA) and proceeded by Duncan Range Test. The resultsshowed that P1 had the highest performance on feed efficiency and average daily gain (ADG) parameters.Blood metabolic test showed that blood total protein, cholesterol, and glucose of all rams were normal. Inconclusion feeding rams with mung bean sprout waste as grass substitution have a positive effect on theperformance of the rams production performance.
Keywords: blood metabolic profiles; garut rams; jonggol rams; mung bean sprouts waste; production performance